35/4 square meters by 7/2 meters

Answers

Answer 1
Answer: Area = 35/4  m²

Length = 7/2 m

Area =  length * width

35/4 =  7/2 * width

7/2 * width = 35/4

width = 35/4 ÷ 7/2

width = 35/4  × 2/7 = 5/2

Width = 5/2 m

Related Questions

Solve for y. 1/2y + 5-3/4y=0
11 is what percent of 55
A cone has a diameter of 30 in. and a slant height of 17 in. What is the approximate volume of the cone?
To graph a rate or a ratio from a table how do you determine the scales to use on each axis
If f(1) = 2 and f (n) = f(n-1) +5 then find the value of f (6)

Use absolute value to express the distance between 10 and -4

Answers

Absolute value does not include direction, therefore, does not have a negative sign. Always positive.

The distance between 10 and -4 is 14.

I showed why in the attachment below. 

So, since we do not include the sign, your final answer is 14.

Final answer: 14

What value is the 6 in 49.62

Answers

The value of the "6" in 49.62 is in the tenth place

The value of 6 in 49.62 is 0.6 OR six tenths

What is the sum of 6/13 and 1/8.why is the sum greater then 1/2

Answers

0 < 6/13 < 1/2 
1/2 - 6/13 = 13/26 - 12/26 = 1/26 
6/13 - 0 = 6/13 = 12/26 
1/26 < 12/26, therefore 6/13 should be rounded to 1/2

hope that helped *smiles*


6/13 + 1/8 = 48/104 + 13/104 = 61/104

1/2 = 52/104

52<61 => 52/104 < 61/104


What is the degree of the polynomial?

Answers

Given:

5 z^(3)-2 z^(4)-9 z^(2)+z

To find:

Degree of the polynomial

Solution:

Degree of a polynomial:

The degree of the polynomial is highest power of the variable in the polynomial.

5 z^(3)-2 z^(4)-9 z^(2)+z

Here, the highest power is 4.

The degree of the polynomial is 4.

Six students shared equally the cost of 18 of one of the items in the chart. Each student paid $24. What item did they buy? Explain how you found your answer.Item                             Price
Origami book             $24each
Origami paper            $6per pack
Origami kit                 $8each

Answers


Origami Kit

8 X 18 = 144

divide by 6 students so 144/6 = $24 each

PLEASE HELP! Im not very good at math

Answers

Answer:

The answer provided is incorrect, the mistake is in the division between the monomials x^{(6)/(5)} and x^{(2)/(5)} that is equal to x^{(4)/(5) not x^3, because we must mantain the same base "x" and subtract the expoents that are (6)/(5) - (2)/(5) = (4)/(5).

Step-by-step explanation:

In order to simplify that question we need to multiply, divide and power monomials with the same base "x". When we multiply monomias with the same base we sum the expoents, to divide we subtract the expoents and to power them we multiply the expoents. Therefore to simplify the equations we must do:

(\frac{x^{(2)/(5)}*x^{(4)/(5)}}{x^{(2)/(5)}})^(1)/(2)\n(\frac{x^{(6)/(5)}}{x^{(2)/(5)}})^(1)/(2)\n(x^{(4)/(5)})^(1)/(2)\nx^{(4)/(10)}\nx^{(2)/(5)}

The answer provided is incorrect, the mistake is in the division between the monomials x^{(6)/(5)} and x^{(2)/(5)} that is equal to x^{(4)/(5) not x^3, because we must mantain the same base "x" and subtract the expoents that are (6)/(5) - (2)/(5) = (4)/(5).

Answer:

No the  answer is incorrect.

Step-by-step explanation:

From the question given;

(X^{(2)/(5) } . X^{(4)/(5) }  / X^{(2)/(5) }   )¹/²   

We will start by solving the inner bracket

By the law of indices x^(a)  .  x^(b) = x^(a+b)

X^{(2)/(5) } . X^{(4)/(5) }  = X^{(2)/(5)+(4)/(5)  }   = X^{(6)/(5) }

we will replace X^{(2)/(5) } . X^{(4)/(5) }   by  X^{(6)/(5) }

X^{(2)/(5) } . X^{(4)/(5) }    by  X^{(6)/(5) }

(X^{(2)/(5) } . X^{(4)/(5) }  / X^{(2)/(5) }   )¹/²   = (X^{(6)/(5) }  / X^{(2)/(5) }   )¹/²   

By the law of indices x^(a) /x^(b)  =  x^(a-b)

X^{(6)/(5) }    /    X^{(2)/(5) }  =  X^{(6)/(5) - (2)/(5) }   =   X^{(4)/(5) }

We will replace X^{(6)/(5) }    /    X^{(2)/(5) }    by    X^{(4)/(5) }

(X^{(6)/(5) }    /    X^{(2)/(5) })¹/²   =   ( X^{(4)/(5) })¹/²    =    X^{(4)/(10) }  =   X^{(2)/(5) }

(X^{(2)/(5) } . X^{(4)/(5) }  / X^{(2)/(5) }   )¹/²   =  X^{(2)/(5) }

  

No the  answer is incorrect.

He made a mistake, because X^{(6)/(5) }    /    X^{(2)/(5) }   =   =  X^{(6)/(5) - (2)/(5) }   =   X^{(4)/(5) }       and   not equal to x^(3)